Ethnoscientific Study of the Making of Traditional Uwi Kaju Ndota and Alu Ndene Food in Ende Regency - Veronika P. Sinta Mbia Wae; Melania Priska; Maimunah H. Daud (Postgraduate, University of Mataram, 2024)
Uwikajundota and alundene are local wisdom based on traditional food whose existence has experienced a shift due to developments over time. Uwikajundota and alundene are traditional foods made from cassava. This research aims to explore scientific concepts in the processing process through an ethnoscience approach. This research is a type of qualitative descriptive research. The location of this research is in Nanganesa village, Ndona District, Ende Regency. The subject of this research is Nanganesa Village while the object is ethnoscience in making the traditional food uwukajundota and alundene. The sampling technique uses purposive sampling. Research data comes from primary data and secondary data. Primary data was obtained from interviews with residents who process uwikajundota and alundene as well as observations regarding the manufacturing process. Secondary data was obtained from literature studies related to theory and other supporting data. Data analysis was carried out through several stages, namely collection, reduction, presentation, and conclusion. The research results show that the stages of making the traditional food uwikajundota and alundene have the potential to be used as a science learning resource. As a science learning resource, the manufacture of uwikajundota and alundene can be studied in several concepts, namely food nutrition, additives, force and pressure, and thermodynamics.